2016
DOI: 10.1016/j.surg.2015.10.011
|View full text |Cite
|
Sign up to set email alerts
|

A network meta-analysis comparing perioperative outcomes of interventions aiming to decrease ischemia reperfusion injury during elective liver resection

Abstract: Network meta-analysis articleThe paper is not based on a previous communication to a society or meeting. Conflicts of Interest and Source of Funding:No conflicts of interest. No external funding.Keywords: ischemia-reperfusion injury, hepatectomy, systematic review, ischemic preconditioning, morbidity, blood loss. Excellence Decision Support Unit. Odds ratios for binary outcomes and mean differences for continuous outcomes were calculated using fixed-effect model or random-effects model according to model-fit.R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 47 publications
0
18
0
2
Order By: Relevance
“…A recent meta-analysis confirmed that hepatic preconditioning (i.e. intermittent vascular inflow occlusion) results in less intraoperative blood loss and a shorter operating time in comparison to hepatectomy alone, but without improved postoperative outcome [140]. Prolonged clamping should nonetheless be avoided since ischemia-reperfusion injury has been shown to induce severe hepatic damage [141].…”
Section: Providing Optimal Perioperative Carementioning
confidence: 99%
“…A recent meta-analysis confirmed that hepatic preconditioning (i.e. intermittent vascular inflow occlusion) results in less intraoperative blood loss and a shorter operating time in comparison to hepatectomy alone, but without improved postoperative outcome [140]. Prolonged clamping should nonetheless be avoided since ischemia-reperfusion injury has been shown to induce severe hepatic damage [141].…”
Section: Providing Optimal Perioperative Carementioning
confidence: 99%
“…Ischaemic preconditioning reduces the adverse effects of IRI through previous exposure to a brief period(s) of vascular occlusion. Direct IPC has been shown to reduce IRI in experimental models of warm hepatic IRI [9] and in patients undergoing major liver resections [10, 11]. However, experimental studies have shown that direct IPC through clamping of the portal inflow vessels may impair liver regeneration [12, 13] and in a multivariate analysis of patients undergoing liver resection, this was found to be an independent predictor for increased post-operative morbidity [14].…”
Section: Introductionmentioning
confidence: 99%
“…10,31 In fact, local ischemic preconditioning before liver resection significantly reduced intraoperative bleeding in one RCT 35 and one meta-analysis. 91 However, a previous meta-analysis showed no effect of local ischemic preconditioning on bleeding in liver resection. 92 Hence, there is no evidence of reduced thromboembolic risk after local ischemic conditioning in patients undergoing surgery or cardiac procedures.…”
Section: Discussionmentioning
confidence: 99%